2016
DOI: 10.1002/sim.7042
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive design for updating the threshold value of a continuous biomarker

Abstract: Potential predictive biomarkers are often measured on a continuous scale, but in practice, a threshold value to divide the patient population into biomarker ‘positive’ and ‘negative’ is desirable. Early phase clinical trials are increasingly using biomarkers for patient selection, but at this stage, it is likely that little will be known about the relationship between the biomarker and the treatment outcome. We describe a single-arm trial design with adaptive enrichment, which can increase power to demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Adaptive-threshold designs have gained interest in various fields of medicine as they may bring on increased power over fixed thresholds [17]. In the limits of the present study, we conclude that the cumulative use of salivary P. gingivalis, IL-1b, and MMP-8 levels with an adaptive design brings additional power over fixed thresholds of single biomarkers in detecting periodontitis.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Adaptive-threshold designs have gained interest in various fields of medicine as they may bring on increased power over fixed thresholds [17]. In the limits of the present study, we conclude that the cumulative use of salivary P. gingivalis, IL-1b, and MMP-8 levels with an adaptive design brings additional power over fixed thresholds of single biomarkers in detecting periodontitis.…”
Section: Discussionmentioning
confidence: 53%
“…The CRS method supports the idea of assigning study population-based thresholds with a more personalized approach, instead of using universal thresholds [17]. It was observed that, there are four-to nine-fold differences between the levels of given thresholds in studies using different methods for these biomarker determinations [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 85%
“…Acknowledging that different patients may require different care has led to trial designs that incorporate assessment of treatment effects in different subsets of the population. Most statistical methodologies for such designs focus on hypothesis testing . In this paper, we have considered point estimation following an adaptive threshold enrichment clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…They utilize the Bayesian method to estimate the threshold of a biomarker which is not normally distributed but follows a Student‐ t distribution and a mixture of Dirichlet processes. Spencer et al (2016) create a design which can learn from the biomarker and make adjustments on the threshold optimally using the combination of Bayesian prediction and the generalized linear model. This design aims to figure out the subpopulation for which the treatment is effective and estimate the threshold parameter.…”
Section: Introductionmentioning
confidence: 99%